Optimalisasi Sistem Manajemen Persediaan untuk Pengendalian Stok yang Efisien Menggunakan Metode FIFO - Fikri Hamidy (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2024)
Inventory of goods is a number of materials or products stored by a company to support its business operations. This inventory can be in the form of raw materials, semi-finished goods, or finished goods that are ready to be sold to customers. Too much inventory can lead to high storage costs and the risk of goods becoming obsolete, while too little inventory can lead to production disruptions or lost sales opportunities. This research aims to optimize the inventory management system to achieve efficient stock control by applying the FIFO method, this research is expected to contribute to improving better inventory management, reducing losses, and supporting smarter decision-making in controlling stock of goods. The results of the test conducted using the Delone and McLean model, the Inventory Management System Optimization system with the FIFO Method obtained an excellent overall score. The 100% results for the System Quality, Usage, and Net Impact dimensions, show that this system is very effective, efficient, and has a positive impact on inventory management. However, there are areas that can be improved in Information Quality, Service Quality, and User Satisfaction, with scores of 80% each. This shows that while the tests show positive results, there is still some room for improvement in the presentation of information, technical support, and user interface to improve the overall experience.